2023
DOI: 10.1002/msc.1735
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of uncertainty amongst musculoskeletal physiotherapists in first contact practitioner roles within primary care

Abstract: AimThe aim of this research was to explore the experiences of uncertainty amongst Musculoskeletal First Contact Practitioners working in primary care.BackgroundThe Musculoskeletal First Contact Practitioner role involves advanced physiotherapists providing an alternative to the GP by acting as first point of contact for people presenting to primary care with musculoskeletal conditions. Limited research into the role exists but the first‐contact aspect, clinical complexity and time pressures are deemed to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Visual posts were reported by participants as being most engaging, aligning with a 2019 systematic review which found that healthcare professionals believe infographics reduce the time burden of reading full texts [31]. Social connection with peers, researchers, and opinion leaders through following, retweeting and liking posts was seen as important in the FCP context, as most work in isolation away from FCP peers and many split their time working across multiple practices [13,14,15]. Participants described feeling reassured when reading tweets relating to clinical questions, evidence and constantly changing policy and guidance for the FCP role; findings useful in light of recent interviews with FCPs exploring common feelings of uncertainty regarding the FCP context and role [13,14].…”
Section: Principle Results and Comparison With Prior Workmentioning
confidence: 77%
See 2 more Smart Citations
“…Visual posts were reported by participants as being most engaging, aligning with a 2019 systematic review which found that healthcare professionals believe infographics reduce the time burden of reading full texts [31]. Social connection with peers, researchers, and opinion leaders through following, retweeting and liking posts was seen as important in the FCP context, as most work in isolation away from FCP peers and many split their time working across multiple practices [13,14,15]. Participants described feeling reassured when reading tweets relating to clinical questions, evidence and constantly changing policy and guidance for the FCP role; findings useful in light of recent interviews with FCPs exploring common feelings of uncertainty regarding the FCP context and role [13,14].…”
Section: Principle Results and Comparison With Prior Workmentioning
confidence: 77%
“…Social connection with peers, researchers, and opinion leaders through following, retweeting and liking posts was seen as important in the FCP context, as most work in isolation away from FCP peers and many split their time working across multiple practices [13,14,15]. Participants described feeling reassured when reading tweets relating to clinical questions, evidence and constantly changing policy and guidance for the FCP role; findings useful in light of recent interviews with FCPs exploring common feelings of uncertainty regarding the FCP context and role [13,14]. Many expressed a fear of missing out on something on Twitter, perhaps echoing this uncertainty.…”
Section: Principle Results and Comparison With Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The term ‘triage’ was used by nine sources, five of which used the term on its own (Bater & Sellars, 2022; iCSP 1‐3, 2021; McDermott et al., 2022), two of which used the term ‘reception triage’ (Doran, 2021a; Halls et al., 2020), and two of which used the term ‘GP triage’ (R. Goodwin et al., 2021; Greenhalgh et al., 2020). ‘Patient self‐referral’ or ‘self‐booking’ was used by four sources (Akehurst et al., 2019; Doran, 2021b; Halls et al., 2020; Jagosh et al., 2022), and ‘GP referral’ or GP involvement in the patient accessing an FCP appointment was referred to in seven sources (Doran, 2021a; R. Goodwin et al., 2021; Greenhalgh et al., 2020; Halls et al., 2020; iCSP 1‐3, 2021; Pike, 2020). Involvement of Reception was stated as an access method in five of the sources (Hensman‐Crook, 2019; iCSP 1, 2021; Jagosh et al., 2022; Pike, 2020; Wise, 2019), for example, direct from reception and booked via reception.…”
Section: Resultsmentioning
confidence: 99%
“…Personnel involved in patients accessing FCP appointments were described as ‘reception/receptionists’ or ‘admin/administration/administrators’ in 17 of the sources (Bater & Sellars, 2022; CSP, n.d.; Davies et al., 2021; Doran, 2021a, 2021b; Goodwin, n.d.; R. Goodwin et al., 2020; Halls et al., 2020; HEE, 2020; Hensman‐Crook, 2019; Jagosh et al., 2022; McDermott et al., 2022; Morris et al., 2021; Pain, 2022; Pike, 2020; Wise, 2019; Ingram et al., 2023), GPs in 10 of the studies and other materials (Doran, 2021b; R. Goodwin et al., 2021; Greenhalgh et al., 2020; Halls et al., 2020; iCSP 1‐3, 2021; McDermott et al., 2022; Pike, 2020), ‘ANPs’ in three (R. Goodwin et al., 2020; Halls et al., 2020; iCSP 1, 2021), ‘primary care team’ in one (CSP, n.d.), and ‘healthcare staff’ in one (R. Goodwin et al., 2020). Three of the studies did not provide any information regarding personnel involved (Akehurst et al., 2019; Bater & Sellars, 2022; Wood et al., 2022).…”
Section: Resultsmentioning
confidence: 99%